Practice based research in dentistry: an alternative to deal with clinical questions - Flávio Fernando DEMARCO; Marcos Britto CORREA; Maximiliano Sérgio CENCI; Frederick James Trevor BURKE; Niek Johannes Maria OPDAM; Andre Luis FARIA- (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Clinical interventions in dental practice should be determined based on the best scientific evidence available. Well-designed randomized clinical trials (RCTs) provide important evidence supporting the efficacy of interventions and are usually considered as the best primary evidence. However, the strict criteria adopted by most RCTs reduce their external validity since some findings from these studies might not work under usual conditions. On the other hand, practice-based research (PBR) studies have been designed to better define the effectiveness of clinical interventions under settings closer to "real-world" conditions. Therefore, this review aimed to describe different PBR designs discussing some advantages and limitations of such studies. The stimulus to organization PBR networks is discussed since the studies performed by these networks involve large number of clinicians and important conclusions can be drawn. Designs of observational studies including surveys and cohort studies based on practice are presented. Survey methods are important to know the behavior of practitioners regarding diagnostic and decision of treatment. Cohorts allow assessing different cofounders contributing to some outcome since large sample sizes and long follow-up periods can be observed in some of these studies. Pragmatic trials designed to take place in real-world clinical practice settings are also discussed as a useful design to assess the effectiveness of clinical interventions. In conclusion, this review sought to present PBR studies as alternative designs to answer clinical questions, but not replacing randomized clinical trials.